Tiwah Ceremony as Hindu Kaharingan Practices in Contemporary Dayak Ngaju Society of Kapuas Regency - Adithiya Wiradinatha Saputra; Lambok Hermanto Sihombing (Jurnal Penelitian Agama Hindu, 2022)
This research discusses about Tiwah ceremony. Tiwah is a ceremony originating from the Dayak tribe in Central Kalimantan to deliver the spirits of the dead to Heaven. In the contemporary that is increasingly developing, the existence of the Tiwah ceremony is very much felt by the existence of social media such as YouTube and Facebook. In this study, we will examine how the influence of social media on the existence of the Tiwah ceremony. This research is very important to do considering the swift currents of modernization which have a big influence on the existence of the ceremony. The purpose of this study is to find out how much influence the social media used by the community has on the traditional ceremony at this time. The data used comes from YouTube and Facebook media about the Tiwah ceremony in Kapuas Regency which was selected randomly based on the number of views, the number of likes, as well as interviews with several informants. This study uses the imagined community theory proposed by Benedict Anderson to understand the sense of nationalism of the people of Kapuas Regency regarding the Tiwah ceremony. Based on our findings, the Dayak Ngaju tribe in Kapuas Regency strongly supports the existence of the Tiwah ceremony through YouTube and Facebook social media with broadcast content, through this indirectly the people in Kapuas Regency strive to continue to introduce the Tiwah ceremony as a form of maintaining and preserving Dayak tribe customs.